A Peer Tutoring Program for Mathematical Problem-Solving - Clara Bastart Jané; Marta Flores Coll (Revista Electrónica de Investigación Educativa)
This study explores the development of cooperative mathematical problem-solving by participants in the “Razonar en pareja” educational program, which is based on cooperative peer tutoring. The research includes a pretest-posttest quasi-experimental study, coupled with a qualitative approach that analyzes interactions between students to detect the influence of mathematical discourse on the variable studied. Progress is observed in participant discourse, with statistically significant improvements in students’ cooperative problem-solving. The study supports a positive influence of peer tutoring on the development of mathematical competence through the program.